Responsabilidade social corporativa e gaps de percepção: um estudo de caso - Pena, Rafael Columa Meirelles (2013)
The expression Corporate Social Responsibility has been commonly used for people , and actions related to CSR are frequently revealed b y companies, and it shows the potential that exists on organizations to influence social and environmental problems. Nowadays there are many metrics that helps companies to measure the effectiveness of Corporate Social Responsibility actions and , with the se metrics, organizations can publish it s performance on public reports for investors and market. The present research is proposed to analyze the performance of a logistic company in Corporate Social Responsibility using its employees perception about this subject, comparing this with the company’s speech , and verifying if there are any gaps between them. P ossible causes for gaps between employees perception a nd company’s speech are analyzed and explained in accordance to the Frankfurt School Theories and o ther researches in Social Responsibility area. Ethos Institute’s Key Performance Indicators are used to delimitate the scope of the research and identify the analyzed company’s performance in Corporate Social Responsibility.